PENGARUH STRATEGI PROMOSI MELALU SOCIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE MS-GLOW YANG DIMEDIASI WORD OF MOUTH DI KABUPATEN GIANYAR - Kadek Dwi Payani; Dewiwati Sujadi (Universitas Triatma Mulya, 2021)
This research purposes to identity the effect of promotional strategies through social media mediated by word of mouth marketing on purchase Ms-Glow in Gianyar. Word of mouth marketing is an activity to discuss satisfaction or dissatisfaction with others. In order to achieve the company goals, it is also necessary to promote through good social media, so that it is stored in the minds of consumers in order to improve purchasing decisions. This research design is a quantitative research. Sampling was using purposive sampling technique, where the total sample size is 100. In this research, statistical analysis is using SPPS (Statistical for Social Science) version 26 computer program. The results of this research indicate that (1) There are a positive influence on promotional strategies through social media, on the decision to purchase Ms-Glow in Gianyar. This is evidence by the t-count of 2,295 with a significance value of 0,024 less than 0,05 and the regression coefficient having an positive value of 0,187 (2) There are a positive effect of promotional through social media on word of mouth marketing on Ms-Glow in Gianyar. This evidenced by the t-count of 6,992 with a significance value 0,000 less than 0,05 and the regression coefficient has a positive value of 0,486. (3) There are a positive effect of word of mouth on Ms-Glow in Gianyar. This is evidenced by the t-count of 3,87 which is greater that t table with a significant level of 0,05, which is 1,96 and the mediation coefficient of 0,24543 is positive.